(untitled) (Bangladesh Journal of Agricultural Research, 2014)
Area shift in favour of fruits has been suggested as a viable option to stabilize and raise farm income, enhance agricultural growth, and increase employment opportunities. Studies on micro-level decision taking for area shift in favour of fruits are very scanty. Therefore, an attempt was made to assess the socioeconomic status of jujube farmers, relative profitability of jujube cultivation, and factors influencing the shifting lands from cereal to jujube cultivation. The study was conducted in three districts, namely Pabna, Natore and Chapai Nababgonj during 2012-13. A total of 180 farmers taking 60 from each district were selected randomly for the study. The per hectare costs of jujube cultivation were Tk. 2,77,232 in the 1st year; Tk. 2,27,925 in the 2nd year; and Tk. 1,90,217 in the 3rd year. The average yields of jujube were found highest in the 3rd year (15.54 t/ha) followed by 2nd year (9.96 t/ha). Per hectare net returns from jujube cultivation were Tk. 1,45,978 in the 2nd year and Tk 3,45,720 in the 3rd year. The total cost of jujube cultivation was around 50% higher than the costs incurred for different cropping patterns. The net return of jujube cultivation was 57% higher compared to different cropping patterns. The shifting of cereal lands to jujube cultivation was reported to be a profitable enterprise as indicated by higher BCR (1.47), net present value (Tk. 2,31,791), and internal rate of return IRR (94%) of jujube cultivation. Relative income and education turned out to be positively significant, whereas age and food crop requirements at home negatively significant for shifting decision from cereal crops to jujube cultivation. Disease and insect infestation, lack of training facilities, and lack of access to credit were the major constraints for jujube cultivation. Jujube cultivation may be encouraged from state authority to increase farmers? income. DOI: http://dx.doi.org/10.3329/bjar.v39i2.20427 Bangladesh J. Agril. Res. 39(2): 243-262, June 2014